PROCALCITONIN TEST IN DIFFERENTIAL DIAGNOSTICS OF ALLERGOSEPSIS SYNDROME - A.M. Chomakhidze; E.I. Alexeeva ("Paediatrician" Publishers LLC, 2007)
The article is devoted to the problem of differential diagnostics for infection and autoimmune nature of the allergosepsis syndrome. In the research, the authors used bramspctq semicquantic tative immunostratographic test to identify procalcitonin, a highly sensitive lab marker for the sepsis and severe bacterial infection growth. They examined 32 patients: 19 of them, suffering from allergosepsis syndrome and having no verified diagnosis, 13 of them, suffering from an inflammation of the systemic (allergoseptic) presentations of the juvenile arthritis. the positive procalcitonin test (over 2 ng/ml) disclosed allergosepsis syndrome among 5 patients and juvenile arthritis among 4 patients. It witnessed the existence of the generalized bacterial infection, as well as it was a sufficient ground for prescription of the antibacterial medications. The negative procalcitonin test (lower than 0.5 ng/ml) was performed among 10 patients, suffering from allergosepsis syndrome, and 9 patients, suffering from juvenile arthritis, witnessed autoimmune nature of the allergosepsis syndrome, as well as it was a sufficient ground for prescription or correction of the immunoreduction therapy. Application of the procalcitonin test among children, suffering from allergosepsis syndrome, allowed for the differential diagnosis between the generalized bacterial infection and active autoimmune process along with the duly prescription of antibacterial and immunoreduction therapy.Key words: allergosepsis syndrome, sepsis, juvenile rheumatoid arthritis, procalcitonin test, children.